Occurrence of Temnocephala Blanchard, 1849 (Rhabdocoela, Temnocephalidae) in Aegla spinosa Bond-Buckup and Buckup, 1994 (Decapoda, Anomura) in Santa Catarina, Southern Brazil. - Marinho de Quadros, Rosiléia (2024)
The aeglids are freshwater crustaceans, playing an important role in the trophic chain for various invertebrate and vertebrate organisms. A specimen of Aegla spinosa Blond-Buckup & Buckup, 1994, from the interior of the municipality of Bocaina do Sul, state of Santa Catarina, was brought to the Laboratory of Parasitology and Zoology at the University of Planalto Catarinense (UNIPLAC). The examined crustacean presented three specimens of Temnocephala. As these animals are vulnerable to environmental changes and alterations in the natural landscape due to anthropic pressure, knowing the presence of temnocephalids can contribute to understanding the associations between these organisms and their hosts, especially in the state of Santa Catarina, where there is a lack of descriptions for the invertebrate fauna.